Vibration and Noise Radiation Characteristics of Gear Transmission System. Issue 4 (December 2014) - Zhou, Jianxing; Wenlei, Sun
This paper presents a comprehensive procedure to calculate steady dynamic response and noise radiation generated by a gear reducer. In this process, the bearing force is obtained by solving the transmission system dynamic model, which is taken as the excitation of the gearbox, the noise generated by the gearbox vibration is researched by using FEM/BEM, so the dynamic characteristics of gear transmission and gearbox structure are demonstrated. Then the time history of node dynamic response and noise spectrum of the gearbox are obtained, and the effect of the excitation of frequency doubling of mesh frequency on the gearbox vibration and noise radiation is illustrated. The changes in radiated noise of gear reducers with load are calculated respectively by using both simulation and Kato's formulae, and results agree well with each other. The frequency range of the gearbox resonance is obtained by analyzing the spectral maps of the vibration and noise under the case of engine speed steadily increased. The study provides useful theoretical guideline to the design of the gearbox.